2018
DOI: 10.1007/s10047-018-1063-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption during hypothermic and subnormothermic machine perfusions of porcine liver grafts after cardiac death

Abstract: The use of grafts donated after cardiac death (DCD) would greatly contribute to the expansion of the donor organ pool. Machine perfusion (MP) is a promising technology to improve DCD liver grafts. Several perfusion technologies under various temperature and oxygenation conditions have been suggested and are still debated. It is important to confirm the relationship between oxygen consumption and organ conditions during MP. In this study, we analyzed oxygen consumption during oxygenated MP of porcine DCD liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Oxygenated SNMP improves not only the oxygen uptake but also the adenosine triphosphate content and reduces the lactate levels of the donor liver [13,14]. Our previous study showed that the oxygen consumption was related to the graft temperature and associated with the effluent LDH level [23]. However, hypothermic conditions seem to have limited utility in graft preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenated SNMP improves not only the oxygen uptake but also the adenosine triphosphate content and reduces the lactate levels of the donor liver [13,14]. Our previous study showed that the oxygen consumption was related to the graft temperature and associated with the effluent LDH level [23]. However, hypothermic conditions seem to have limited utility in graft preservation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of this combination on tissue lesions in the late phase suggest that an intermediate oxygenation level could be more efficient. Perfusion supplementation with M101 and O 2 could also be valuable in other conditions, such as a sub-normothermic situation, which has been reported as being better than hypothermic perfusion in terms of organ preservation quality, as suggested by Morito et al [31]. Finally, these findings are potentially applicable to other organs, such as liver, for which MP techniques are just emerging.…”
Section: Discussionmentioning
confidence: 76%
“…In our system, each hepatic artery (HA) and portal vein (PV) was perfused. Details of our system are reported in previous papers [9,10]. Each circuit consisted of a roller-type pump (MasterFlex7520-40; Cole-Parmer, Bunker Court, IL, USA), an electrical flow meter (VN05; Aichi Tokei, Aichi, Japan for PV; FD-SS02; Keyence, Osaka, Japan for HA), a ceramic capacitive pressure sensor (KL76; Nagano Keiki, Nagano, Japan), and an air trap developed in-house.…”
Section: Machine Perfusion Systemmentioning
confidence: 99%
“…Each circuit consisted of a roller-type pump (MasterFlex7520-40; Cole-Parmer, Bunker Court, IL, USA), an electrical flow meter (VN05; Aichi Tokei, Aichi, Japan for PV; FD-SS02; Keyence, Osaka, Japan for HA), a ceramic capacitive pressure sensor (KL76; Nagano Keiki, Nagano, Japan), and an air trap developed in-house. An oxygenator (HP0-06 H-C; Senko Medical Instrument, Tokyo, Japan) was installed in the circuit for the PV and HA [10]. The flow rate of the PV was 0.22 mL/min/g and that of the HA was 0.06 mL/min/g.…”
Section: Machine Perfusion Systemmentioning
confidence: 99%
See 1 more Smart Citation